Attitudes of relatives of mucopolysaccharidosis type III patients toward preconception expanded carrier screening - Nijmeijer, Stephanie C. M. (Eur J Hum Genet, 2020)
Preconception expanded carrier screening (ECS) aims to detect carrier couples of autosomal recessive (AR) disorders before pregnancy in order to increase reproductive autonomy of prospective parents. Genetic knowledge and knowledge gained from experience influence decision making on participation in genetic testing and understanding carrier test results. In this study we assessed whether parents and relatives of patients with the severe AR condition mucopolysaccharidosis type III (MPS III), who are expected to have genetic and experiential knowledge, have more positive attitudes toward ECS than the Dutch reference group. Parents of all MPS III patients known to the Dutch expert center were invited to participate and asked to invite first and second degree relatives. The online questionnaire started with an educational text, and assessed attitudes toward ECS, genetic knowledge and perceived MPS III severity. Results were compared with the Dutch population. Parents and relatives of MPS III patients (n = 159) scored higher on the genetic knowledge test and perceived MPS III as more severe compared with the general Dutch population (n = 781). Parents and relatives reported to be more likely to participate in ECS (84.3% and 62.5%, respectively) compared with the public (31%) (p < 0.001). Being a relative of a MPS III patient was the strongest variable in the regression analyses for intended ECS participation. Our results show that genetic knowledge influences ECS decision making. Therefore, appropriate information on ECS and genetic counseling is needed to enable prospective parents from the general population, including relatives of patients with severe hereditary disorders, to make informed decisions.